Activity-Based Approach Method to Improve Class I Student Learning Outcomes - Fatoni Fatoni (Madrosatuna: Journal of Islamic Elementary School, 2017)
Student activities in teaching and learning activities are absolutely necessary. But even more important in increasing student activity is the teacher's ability to plan a teaching and learning activity to achieve learning goals. Based on these phenomena, researchers will conduct an action research activity on students of class I Sengon 1 SDN Jombang Regency emphasizing on increasing student learning motivation through activity-based learning activities. The researcher uses the observation method or observes objects directly in the classroom with action research methods. Based on the research activities of the actions that have been carried out by researchers, conclusions can be formulated, including: 1) Learning strategies with Teaching Approaches Based on Natural Activities Islamic Education Learning Standards Competence "Memorizing Short Letters" Class I students of Sengon 1 Elementary School Jombang Regency can improve achievement of learning outcomes, motivation, creativity, and problem solving in, learning; 2) Positive impacts obtained from activity-based learning strategies are: (1) students are more motivated in learning, (2) students are more creative, (3) students are more willing to express and answer questions, (4) students are more responsible, and (5) learning achievement increases. While the negative impact is that students who lack creativity and low ability will always be left behind in the learning process. On the other hand, students who are more creative and have more abilities will feel good compared to students below.